151k views
2 votes
Select all the equations that are equivalent to−3(x+1)

A.-3x+(-3)
B.x-3
C.-3x+1
D.-3x-3

User Adilbo
by
5.1k points

1 Answer

6 votes

A) - 3x + (- 3) and D) - 3x - 3 are equivalent.

Explanation:

We have,

− 3( x + 1)

= − 3x - 3

A. - 3x + (-3)

= − 3x - 3, is equivalent to − 3( x + 1).

B. x - 3

= x - 3, is not equivalent to − 3( x + 1).

C. - 3x + 1

= - 3x + 1, is not equivalent to − 3( x + 1).

D. - 3x - 3

= - 3x - 3, is equivalent to − 3( x + 1).

Thus, A) - 3x + (- 3) and D) - 3x - 3 are equivalent.

User SebDieBln
by
5.0k points